Response of Azotobacter beijerinckii C4 to oxidative stress of Cd2+, acetochlor and their association - XUAN Ying; MIN Hang; LÜ Zhen-mei; YAN Bo (浙江大学学报. 农业与生命科学版)
The activity response of the antioxidant enzymes of Azotobacter beijerinckii C4 (G-) following exposure to Cd2+, acetochlor and their associations was investigated. Results showed that activities of SOD, CAT and ATPase in the bacterium were induced positively and obviously by Cd2+ or acetochlor, especially at the beginning time after treatment. The associated pollution of Cd2+ and acetochlor had different impacts on the activity of the antioxidant enzymes with different concentrations and treatment time. SOD and ATPase activities by the associations appeared stronger than each of their single factor, and the activities were consistent with each of their single factor finally. It presented induced or inhibited actions on CAT activity by various concentration associations, and appeared inhibiting effect ultimately.